Differential Responses of Wheat (Triticum aestivum L.) and Cotton (Gossypium hirsutum L.) to Nitrogen Deficiency in the Root Morpho-Physiological Characteristics and Potential MicroRNA-Mediated Mechanisms - Xue, Huiyun; Liu, Jia; Oo, Sando; Patterson, Caitlin; Liu, Wanying; Li, Qian; Wang, Guo; Li, Lijie; Zhang, Zhiyong; Pan, Xiaoping; Zhang, Baohong (Frontiers in Plant Science, 2022)
Understanding the potential mechanism of crops to N-deficiency tolerance is very important for developing sustainable agriculture. In addition, it is unclear if the potential microRNA-mediated mechanism related to root growth comply with a common mechanism in monocots and dicots under N deficiency. Therefore, the root morpho-physiological characteristics and potential microRNA-mediated mechanism of wheat (Triticum aestivum L.) and cotton (Gossypium hirsutum L.) were studied under N deficiency. Except the root dry weight, shoot dry weight, plant dry weight, total leaf area, oxygen consuming rate in root and leaf physiological traits of both crops almost significantly decreased after 8 days N deficiency. Although N deficiency didnot significantly impact the root biomass, an obvious change on the root morphological traits was observed in both wheat and cotton. After 8 days of treatment with N deficiency, the total root length, root surface area, root volume per plant of both crops had an opposite trend with significantly decreasing in wheat while significantly increasing in cotton, accompany with the seminal root length per plant in wheat and the primary root length per plant in cotton both increasing, while the lateral root density significantly increased in wheat but significantly decreased in cotton. Additionally, the two crops had different root regulatory mechanisms of miRNAs to nitrogen deficiency. In wheat, the overexpression of miR167, miR319, miR390, miR827 and miR847 inhabiting the total root growth but promoting the seminal roots growth and lateral root formation to tolerate nitrogen deficit. In cotton, overexpression of miR156, miR396, miR171, miR172, miR390 and reduced expression of miR162 and miR393 are contributed to increase in the total root and primary root growth while decrease in the lateral root formation to adapt the nitrogen deficit. In conclusion, N deficiency significantly affected the morpho-physiological characteristics of roots which potentially regulated by microRNA, but the miRNA-mediated mechanism was different in wheat and cotton.